Human errors in maintenance activities: An overview of some contributing factors and plans to mitigate their effects - Sasitharan, D.; Mad Lazim, Halim (UUM College of Business, 2016)
This paper was intentionally designed to highlight the human as the aspects that lead to errors in maintenance practices.It is important to consider the human factor in maintenance activities in order to help minimize their errors and promote a safe working environment.In this regard, the maintenance strategy versus maintenance practices has been acknowledged by many researchers as an excellent key consideration for human factors programme. Consequently, this paper will explain the important considerations on the factors that influence human errors in maintenance programs and provide suggestions to reduce these occurrences.